2016
DOI: 10.4025/actascitechnol.v38i1.27103
|View full text |Cite
|
Sign up to set email alerts
|

<b>Impact of electrical stunning on fish behavior and meat quality of pacu (<i>Piaractus mesopotamicus</i>)

Abstract: ABSTRACT. Electrical stunning is considered one of less stressful fish stunning method. However, for its efficiency, it is important to determine the best way of application of the electrical variables. The aim of this study was to evaluate the effect of different voltages (100, 150, and 200 V) of alternating current (AC) or direct current (DC), frequency of 50 Hz, for 180 s exposure, concerning the aspects of behavior and meat quality of pacu (Piaractus mesopotamicus). Fish subjected to AC remained unconsciou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…For electrical stunning (ES), although an apparent loss of consciousness was observed after 30 s of exposure, visualized by the absence of movement, the electrical current was maintained for 180 s (3 min) to ensure the unconsciousness during bleeding. This protocol was used by Oliveira Filho et al (2016), who reported a recovery of consciousness of pacu after 4 min, which is enough time to be used by the fish processing industries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For electrical stunning (ES), although an apparent loss of consciousness was observed after 30 s of exposure, visualized by the absence of movement, the electrical current was maintained for 180 s (3 min) to ensure the unconsciousness during bleeding. This protocol was used by Oliveira Filho et al (2016), who reported a recovery of consciousness of pacu after 4 min, which is enough time to be used by the fish processing industries.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, very strong electrical current or long exposure times can result in blood spots in fillets, decreasing the commercial value (Zampacavallo et al, 2015). Therefore, for this stunning method to be effective, all technical parameters, such as intensity, type of current and frequency must be well adjusted for each fish species (Oliveira Filho et al, 2016; Venturini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid accumulation in fish muscle may be considered in response to over‐activity, particularly in T3 group (Wendelaar Bonga, ). Fish material of the experiment being a white muscle fish shows that the anaerobic glycolysis is used to meet the energy needs (Oliveira Filho et al, ). As a known condition, the salmon white muscles affected by a stress agent are transformed from the aerobic ATP production to the anaerobic glycolytic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, stunning stress can induce anaerobic metabolism, and increased lactate level can trigger this condition. (Oliveira Filho et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This technique keeps the flesh quality, but causing rapid and violent reaction and an attempt to escape (POLI et al, 2005). Electrical stunning, which consists of passing electric current in water or directly through fish until complete loss of consciousness, is also an alternative for fish stunning (GASCO et al, 2014;MORZEL;SOHIER;VA N DE VIS, 2002;OLIVEIRA FILHO et al, 2016). This technique leads to unconsciousness almost instantaneously.…”
Section: Introductionmentioning
confidence: 99%